How Singing can Help People With Dementia and Their Family Care-Partners: A Mixed Studies Systematic Review With Narrative Synthesis, Thematic Synthesis, and Meta-Integration - Thompson, Zara; Baker, Felicity A.; Tamplin, Jeanette; Clark, Imogen N. (Frontiers in Psychology, 2021)
Background: Recent research on the efficacy of music-based interventions for people with dementia have focused on specific outcomes and methods, and singing has been noted as a particularly beneficial activity. However, due to heterogeneity of research methods, there is a need to synthesize the findings of both quantitative and qualitative research in order to better understand both the impact and potential mechanisms of singing for people in this population. Method: This systematic review included quantitative, qualitative and mixed-methods studies, and analysed these using a systematic mixed-studies synthesis (with a results-based convergent approach). Quantitative and qualitative data were initially synthesized using a narrative synthesis and thematic synthesis method respectively, before a final meta-integration method was used to synthesize common themes across the two data forms. Results: Electronic and hand search strategies revealed 1815 relevant studies, 40 of which met the full eligibility criteria. Narrative synthesis of quantitative data revealed six key outcome areas (quality of life; psychological wellbeing; cognition; engagement; activities of daily living; care-partner wellbeing), and thematic synthesis of qualitative data generated seven themes relating to the impact and mechanisms of singing (pragmatic elements; social benefits; mood; identity; memory; flow-on effects; and relationships). Meta-integration identified four key areas relating to the impact and mechanisms of singing for people with dementia and care-partners: psychological wellbeing, quality of life, cognition and care-partner wellbeing. Conclusion: Results from the syntheses suggest that singing can positively impact the lives of people with dementia and their care-partners, although due to heterogeneity of study design and outcome measures, it is difficult to draw conclusions based on quantitative data alone. Qualitative data provides further context and insights from participant perspectives, and when integrated with quantitative data, reveals contextual factors that may influence the benefits that participants experience from singing. Introduction